2022
DOI: 10.3390/jcm11061746
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Follow Up of the Premature Neonates—Rationale and Practical Issues

Abstract: The aim of the review was to present the state of knowledge about the respiratory pathology in former premature neonates (children that were born preterm—before 37 weeks of gestation—and are examined and evaluated after 40 weeks corrected age) other than chronic lung disease, in order to provide reasons for a respiratory follow-up program for this category of patients. After a search of the current evidence, we found that premature infants are prone to long-term respiratory consequences due to several reasons:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…Late preterm infants, those born between 32 and 36 weeks gestational age, are less likely to develop BPD; however, these infants are still at an increased risk of adverse respiratory outcomes 5 . Chief among these is the development of bronchial hyperactivity presenting as isolated or recurrent wheezing and later development of asthma 5,6 . A previous systematic review found an increased risk of wheezing disorders in preterm babies, with an inverse correlation between gestational age at birth and the risk of wheezing 6 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Late preterm infants, those born between 32 and 36 weeks gestational age, are less likely to develop BPD; however, these infants are still at an increased risk of adverse respiratory outcomes 5 . Chief among these is the development of bronchial hyperactivity presenting as isolated or recurrent wheezing and later development of asthma 5,6 . A previous systematic review found an increased risk of wheezing disorders in preterm babies, with an inverse correlation between gestational age at birth and the risk of wheezing 6 .…”
Section: Introductionmentioning
confidence: 99%
“…5 Chief among these is the development of bronchial hyperactivity presenting as isolated or recurrent wheezing and later development of asthma. 5,6 A previous systematic review found an increased risk of wheezing disorders in preterm babies, with an inverse correlation between gestational age at birth and the risk of wheezing. 6 Another study found that more than 54% of infants born at 32-36 weeks gestation had a physician diagnosis of wheezing within the first 3 years of life, with nearly half of these infants having recurrent wheezing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the current medical technology, mild ventilation techniques can be used to sustain the lives of preterm infants at a lower gestational age (GA). [2,3] Although MV can improve oxygenation and reduce mortality, it is also associated with various complications, including chronic lung injury. [4] Previous studies have mainly focused on the relationships among MV, bronchopulmonary dysplasia (BPD), and lung function.…”
Section: Introductionmentioning
confidence: 99%
“…Previous longitudinal pulmonary function and long-term follow-up studies reported that most extremely/very preterm neonates with BPD present with a low lung function trajectory [13,14] and an increased risk for the future development of a chronic obstructive pulmonary disease (COPD)-like phenotype [15][16][17]. Furthermore, former extremely/very premature infants are predisposed to the development of other respiratory morbidities than chronic lung disease, due to factors associated with prematurity [18]. These infants present with a higher incidence of lower respiratory tract infections requiring re-hospitalizations, impaired lung mechanics, and developmental abnormalities of the airways, leading to recurrent wheezing and asthma.…”
Section: Introductionmentioning
confidence: 99%